Light and immunostimulant mediated in situ re-education of tumor-associated macrophages using photosensitizer conjugated mannan nanoparticles for boosting immuno-photodynamic anti-metastasis therapy. (30th November 2022) - Uthaman, Saji; Pillarisetti, Shameer; Lim, Youn-Mook; Jeong, Jin-Oh; Bardhan, Rizia; Huh, Kang Moo; Park, In-Kyu
Abstract : Novel co-operative immuno-photodynamic therapy nanoparticles, targeting tumor-associated macrophages, modulating the tumor microenvironment, and preventing tumor metastasis by skewing TAMs to M1-like cells, have been developed. Abstract : In an immunosuppressive tumor microenvironment, tumor-associated macrophages (TAMs) are the most abundant cells displaying pro-tumorigenic M2-like phenotypes, encouraging tumor growth and influencing the development of resistance against conventional therapies. TAMs are highly malleable. They can be repolarized into tumoricidal M1-like cells. In this study, we report the synthesis of novel co-operative immuno-photodynamic nanoparticles involving TAM self-targeting acrylic acid grafted mannan (a polysaccharide) conjugated with the chlorin e6 (Ce6) photosensitizer and then loaded with resiquimod (R848), a toll-like receptor (TLR7/8) agonist. The mannan conjugated Ce6 loaded with R848 (MCR) as bioconjugate nanoparticles demonstrated selective targeting of anti-inflammatory M2-like cells. Using photodynamic therapy they were repolarized to pro-inflammatory M1-like cells with combined effects of reactive oxygen species (ROS)-triggered intracellular signaling and a small-molecule immunostimulant. The MCR also demonstrated a TAM-directed adaptive immune response, inhibited tumor growth, and prevented metastasis. Our results indicate that these MCR nanoparticles can effectively target TAMs and modulate them for cancer immunotherapy.